P519 Analysis of the effectiveness and safety of switching from originator to biosimilar adalimumab in patients with Inflammatory Bowel Disease. (21st January 2022) - Casanova, M J; Chaparro, M; Nantes, Ó; Varela, P; Vela-González, M; Montserrat, R; Sierra, O G; Riestra, S; Barreiro-de Acosta, M; Martín-Rodríguez, M M; Gargallo-Puyuelo, C J; Reygosa, C; et al.
Abstract: Background: Aims: 1) to compare persistence on adalimumab treatment over time in inflammatory bowel disease (IBD) patients who maintained adalimumab reference [non-switch cohort (NC)] vs. those who switched from adalimumab reference to adalimumab biosimilar [switch cohort (SC)]; 2) to compare loss of effectiveness of adalimumab treatment in the NC vs. SC; 3) to identify factors associated with discontinuation of adalimumab therapy; 4) to identify the factors associated with relapse in both cohorts; and 5) to evaluate the safety of both strategies. Methods: Retrospective, observational, multicentre study. Patients under adalimumab reference who were in clinical remission at standard dose of adalimumab reference, and in whom adalimumab was the first anti-TNF administered, were included. Clinical remission was defined as a Harvey-Bradshaw index ≤4 points in Crohn's disease, a partial Mayo score ≤2 in ulcerative colitis, and the absence of fistula drainage despite gentle finger compression in perianal disease. The follow-up time was at least 6 months since start of study observation period. The Kaplan-Meier method with log-rank test was used to evaluate the cumulative incidence of treatment discontinuation. Cox regression model was used to investigate factors potentially associated with therapy discontinuation. Results: A total of 505 patients were included (45% women, 87% Crohn's disease): 229 in the SC and 276 in the NC. The median follow-up was 12 months in the SC and 23 months in the NC ( p <0.01). The incidence rate of adalimumab discontinuation was 10% [95% confidence interval (95%CI)=6–14%], and 7% (95%CI=5–10%) per patient-year in the SC and in the NC, respectively ( p =0.035). The probability of maintaining adalimumab was 92% at 12 months and 77% at 24 months in the SC, and 97% at 12 months and 86% at 24 months in the NC. In the multivariable analysis, the switch to adalimumab biosimilar, adjusted for the level of C-reactive protein at baseline, was not associated with therapy discontinuation. 18% of the patients relapsed in the SC vs. 21% in the NC. The incidence of relapse was 17% (95%CI=13–23%) in the SC, and 12% (95%CI=10–16%) per patient-year in the NC ( p =0.04). The cumulative incidence of relapse was 11% at 12 months and 38% at 24 months in the SC, and 11% at 12 months and 22% at 24 months in the NC. In the multivariable analysis, the switch to adalimumab biosimilar (adjusted by type of IBD) was associated with a higher risk of relapse (HR=1.5, 95%CI=1.008–2.36). 4% of the patients had adverse events in the SC vs. 8% in the NC ( p >0.05). Conclusion: The incidence rate of relapse was slightly higher in the SC; however, this fact had no impact on persistence on the drug. Switching from adalimumab reference to adalimumab biosimilar was safe.